2014
DOI: 10.5194/hess-18-3651-2014
|View full text |Cite
|
Sign up to set email alerts
|

Linkages between ENSO/PDO signals and precipitation, streamflow in China during the last 100 years

Abstract: Abstract. This paper investigates the single and combined impacts of El Niño-Southern Oscillation (ENSO) and the Pacific Decadal Oscillation (PDO) on precipitation and streamflow in China over the last century. Results indicate that the precipitation and streamflow overall decrease during El Niño/PDO warm phase periods and increase during La Niña/PDO cool phase periods in the majority of China, although there are regional and seasonal differences. Precipitation and streamflow in the Yellow River basin, Yangtze… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
65
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(74 citation statements)
references
References 49 publications
(60 reference statements)
9
65
0
Order By: Relevance
“…In addition to ONI, PDO was shown to have the greatest impact on stream flow (Figure 8). Ouyang et al [48] illustrated that stream flow and precipitation were relatively lower in the PDO warm phase and higher in the PDO cool phase in the Yangtze River Basin, and the effects of PDO on stream flow was less than ENSO, which is in accordance with our findings.…”
Section: Potential Anthropogenic Impacts On Stream Flow Changessupporting
confidence: 83%
See 1 more Smart Citation
“…In addition to ONI, PDO was shown to have the greatest impact on stream flow (Figure 8). Ouyang et al [48] illustrated that stream flow and precipitation were relatively lower in the PDO warm phase and higher in the PDO cool phase in the Yangtze River Basin, and the effects of PDO on stream flow was less than ENSO, which is in accordance with our findings.…”
Section: Potential Anthropogenic Impacts On Stream Flow Changessupporting
confidence: 83%
“…Results of our study were consistent with the findings of Wei et al [47], who found the impacts of La Niña events would induce increased stream flow in the Yangtze River Basin. Similar conclusions were also achieved by Ouyang et al [48], and Chen et al [49]. In addition to ONI, PDO was shown to have the greatest impact on stream flow (Figure 8).…”
Section: Potential Anthropogenic Impacts On Stream Flow Changessupporting
confidence: 75%
“…The IOD was first identified in 1999 and affects many nations' climate around the Indian Ocean rim [53][54][55][56][57]. The ENSO index is represented by the Niño interannual ENSO-related teleconnections [58]. The impacts of ENSO in association with PDO on precipitation and streamflow have been found in eastern Australia, South America, and China [58][59][60].…”
Section: Enso Iod and Pdomentioning
confidence: 99%
“…The ENSO index is represented by the Niño interannual ENSO-related teleconnections [58]. The impacts of ENSO in association with PDO on precipitation and streamflow have been found in eastern Australia, South America, and China [58][59][60]. Figure 2 shows the spatial long-term trend distribution of TWS, SM, and precipitation.…”
Section: Enso Iod and Pdomentioning
confidence: 99%
See 1 more Smart Citation